The development of a translational traction rig to investigate the mechanisms of traction in 3G turf - Webb, C.; Forrester, S.; Fleming, P. (Procedia Engineering, 2015)
During football specific movements a high translational traction is desired at the shoe-surface interface to facilitate player movement. Translational traction is commonly assessed through bespoke mechanical test devices which provide a more repeatable tool for characterising the shoe-surface interaction compared to player testing. Following development, application of the rig is demonstrated through an initial investigation into the effect of the number of studs and stud orientation on translational traction. The translational rig consists of a tray attached to two trails, with surface samples of varying specification placed in the tray. A number of stud configurations were chosen and tested on a 3G artificial turf sample. The initial stiffness response of the surface as well as larger displacements were considered to help inform the mechanisms of traction. The study showed the increasing force as the number of studs increased and how the positions of the studs also relate to the forces produced in the infill and the effect on the mechanism of traction.